(3cJGH fUGQi GdTGe dSjOfG YeQ Hf GdNWGH jSCdhfg ajeG GdCeGfs - (3eMeO Hf Rjf GdOjf gdGd GdMfaj,J (B1012 (3g` s ((3CHh GdSYhO s)
(3ChdgG (B:s
(3bO CYWi YHO Gddg YeQ CejQ GdeDefjf ef GdCeGf CeGfkG dCfaSge hcJGHge hUdHGfge SbjekG s
(3BNQgG (B:s
(3hbO CXgQ HYV GdjghO cJGHkG COYhG ajg Cfg cJGH QShd Gddg SGFQ CFeg MOkG bfd s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B12s
(3GdfSNI HgG MhGTs
(3JGQjNs
(3HgG fXGe GdJYbjHI s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdeLGejYs